Pilot your organization using cash flow planning with frequent feedback - Ottosson, Stig (Technovation)
Based on action research in a small Swedish enterprise conducted over some eighteen months, a major financial activity to combat liquidity shortage consists of weekly cash flow planning with frequent feedback. A model for continuous liquidity planning has been derived from this research.